2021
DOI: 10.1183/13993003.04133-2020
|View full text |Cite
|
Sign up to set email alerts
|

Altered pulmonary blood volume distribution as a biomarker for predicting outcomes in COVID-19 disease

Abstract: BackgroundEvidence suggests that vascular inflammation and thrombosis may be important drivers of poor clinical outcomes in patients with COVID-19. We hypothesized that a significant decrease in the percentage of blood vessels with a cross-sectional area between 1.25–5 mm2 (BV5%) on chest computed tomography (CT) in COVID-19 patients is predictive of adverse clinical outcomes.MethodsRetrospective analysis of chest CT scans from 10 hospitals across two state in 313 COVID-19 positive and 195 COVID-19 negative pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…A low TLCO is not exclusively determined by reduced VA ( Nusair, 2020 ), and residual interstitial anomalies ( Chen et al, 2020 ; Mo et al, 2020 ; Qin et al, 2021 ) and pulmonary vascular anomalies (i.e., abnormal capillary-alveolar units) ( Morris et al, 2021 ) may play a fundamental role and this could be also the case in COVID-19 survivors ( Figures 2A , B ). This holds true as the interpretation of low TLCO must consider the complex relationship between VA, TLCO and KCO, and may inopportunely exclude the presence of abnormal gas exchange in the lung ( Figures 2A , B ).…”
Section: Physiology and Pathophysiology Of Abnormal Pulmonary Function Variables As Observed In Covid-19 Survivorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A low TLCO is not exclusively determined by reduced VA ( Nusair, 2020 ), and residual interstitial anomalies ( Chen et al, 2020 ; Mo et al, 2020 ; Qin et al, 2021 ) and pulmonary vascular anomalies (i.e., abnormal capillary-alveolar units) ( Morris et al, 2021 ) may play a fundamental role and this could be also the case in COVID-19 survivors ( Figures 2A , B ). This holds true as the interpretation of low TLCO must consider the complex relationship between VA, TLCO and KCO, and may inopportunely exclude the presence of abnormal gas exchange in the lung ( Figures 2A , B ).…”
Section: Physiology and Pathophysiology Of Abnormal Pulmonary Function Variables As Observed In Covid-19 Survivorsmentioning
confidence: 99%
“…The consequence would be a decrease in both VA and KCO (for that diminished VA). There is mounting evidence for impaired pulmonary hemodynamics in COVID-19 patients ( Potus et al, 2020 ), including vascular pruning, decreased pulmonary blood volume and abnormal pulmonary blood volume distribution as measured via high resolution CT ( Lins et al, 2020 ; Morris et al, 2021 ). Figures 2A , B shows that a decrease in KCO may develop in the context of alveolar-capillary damage, microvascular pathology, or anemia.…”
Section: Physiology and Pathophysiology Of Abnormal Pulmonary Function Variables As Observed In Covid-19 Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies at 6 months indicate that interstitial abnormalities on CT are common 1 . Pulmonary vascular volume is reduced 12 and microvascular imaging using both lung magnetic resonance and DECT suggests that perfusion defects are common at follow‐up 13,14 . The relative contributions of long‐term interstitial and vascular abnormalities to persistent breathlessness remain uncertain, but lone vascular defects are increasingly recognized (Figure 1B,C).…”
Section: Figurementioning
confidence: 99%
“…To our knowledge, such an edema in non-critically ill patients has never been evidenced in vivo. Additionally, the attenuation of small blood vessels is not speci c of SARS-CoV-2-related pneumonia and occurs in any community-acquired pneumonia [11,12]. Indeed, studies of CTPA combined with arti cial intelligence [11,12] have shown a lessering of pulmonary micro-vessels (below 5 mm 2 ) in patients with COVID-19 as well as in community-acquired pneumonia, this decrease being a prognostic factor for the risk of mechanical ventilation or death [11].…”
Section: Introductionmentioning
confidence: 99%